Efeitos do capital humano da indústria de transformação no crescimento econômico no Brasil - Silva, Edcleutson de Souza (2023)
The main objective of this dissertation is to evaluate the influence of human capital employed in the manufacturing industry on economic growth in Brazilian municipalities, and additionally to verify the existence of spillover of this human capital to other sectors of the economy (agriculture and livestock and services), from 2004 to 2019, based on data obtained from RAIS and IBGE. As an econometric strategy, in addition to using panel data with fixed effects control, it is proposed to deal with endogeneity through the use of instrumental variables, specifically the Bartik instrument. The main results indicate that human capital has a positive effect on the economic growth of municipalities and also on spillover to the service sector. In line with the Brazilian empirical literature, this evidence suggests that human capital in the manufacturing industry contributes to economic growth in Brazil.